2012
DOI: 10.3390/ijms131216971
|View full text |Cite
|
Sign up to set email alerts
|

Increased Insulin Sensitivity and Distorted Mitochondrial Adaptations during Muscle Unloading

Abstract: We aimed to further investigate mitochondrial adaptations to muscle disuse and the consequent metabolic disorders. Male rats were submitted to hindlimb unloading (HU) for three weeks. Interestingly, HU increased insulin sensitivity index (ISI) and decreased blood level of triglyceride and insulin. In skeletal muscle, HU decreased expression of pyruvate dehydrogenase kinase 4 (PDK4) and its protein level in mitochondria. HU decreased mtDNA content and mitochondrial biogenesis biomarkers. Dynamin-related protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 54 publications
6
14
0
Order By: Relevance
“…In general, the unloading-induced alterations in mRNA expression levels of constituents of PGC-1 signaling are in line with studies from Cassano et al and a report from Wagatsuma et al that showed that, although ERR-␣ and Tfam mRNA levels were downregulated upon unloading, NRF-1 mRNA levels were unaltered in rat soleus muscle and mouse gastrocnemius muscle, respectively, after 14 or 7 days of unloading (12,45). Qi et al, on the other hand, demonstrated that NRF-1 mRNA levels were potently decreased in rat skeletal muscle after 3 wk of hindlimb suspension (31). No studies so far have investigated the response of Tfam and NRF-1 protein levels upon changes in loading of the musculature.…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxsupporting
confidence: 72%
“…In general, the unloading-induced alterations in mRNA expression levels of constituents of PGC-1 signaling are in line with studies from Cassano et al and a report from Wagatsuma et al that showed that, although ERR-␣ and Tfam mRNA levels were downregulated upon unloading, NRF-1 mRNA levels were unaltered in rat soleus muscle and mouse gastrocnemius muscle, respectively, after 14 or 7 days of unloading (12,45). Qi et al, on the other hand, demonstrated that NRF-1 mRNA levels were potently decreased in rat skeletal muscle after 3 wk of hindlimb suspension (31). No studies so far have investigated the response of Tfam and NRF-1 protein levels upon changes in loading of the musculature.…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxsupporting
confidence: 72%
“…Several studies show that this metabolic flexibility is lost during periods of inactivity as the muscle relies on glucose oxidation rather than fatty acids for energy generation. Thus, the muscles from HU rats show increased utilization of glucose after 2 and 3 weeks of inactivity. These findings may be traced to a shift in muscle fibre types towards fast‐twitch glycolytic fibres.…”
Section: Methodsmentioning
confidence: 85%
“…However, changes in substrate preference probably precede the fibre‐type shift since type I fibres from HU rats exhibit greater utilization of glucose than type I fibres of ground‐based controls during contractile activity . Downregulation of mitochondrial enzymes involved in beta‐oxidation of fatty acids accompany this metabolic shift . At the organelle level, the mitochondrial respiratory capacity is not affected by pyruvate (a carbohydrate derivative) but significantly reduced when a fatty acid substrate is added .…”
Section: Methodsmentioning
confidence: 99%
“…Also included in this issue are papers describing the contributions of ROS and mitochondrial function to other more rare and specific disease states including lupus [8] and epilepsy [9] and chronic regional pain syndrome [10]. Popular topics in this special issue include mitochondrial function [1,2,5,8,11], oxidative stress [2,6,1215], nitric oxide [3,1618], cellular signaling [3,13,19]. In addition there are reports pertaining to endoplasmic reticulum stress [12], hypoxic stem cell niches [20], adaptive responses to oxidative stress [21], and a paper describing a Columbian medicinal plant that inhibits lipid peroxidation [22].…”
mentioning
confidence: 99%
“…In addition there are reports pertaining to endoplasmic reticulum stress [12], hypoxic stem cell niches [20], adaptive responses to oxidative stress [21], and a paper describing a Columbian medicinal plant that inhibits lipid peroxidation [22]. There are papers relating to the role of ROS and nitric oxide in different organ systems including brain [7,15], muscle [11,17], as well as papers detailing the role of reactive oxygen and free radical biology in mediating the toxicity of ischemia [13]. Finally, there are three papers that present significant technical advances; two on the in vivo detection of ROS [15,23], and one that introduces an advanced Electron Spin Resonance technique to study lipid peroxidation [24].…”
mentioning
confidence: 99%